PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Imam Hidayat; Mayla Tasliyah (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study aims to examine the factors that influence company value. There are several factors used, including company size, profitability, leverage. The purpose of this study is to empirically examine whether company size, profitability, leverage, influence the value of the company in consumer goods industry companies listed on the Indonesia Stock Exchange. In this study experienced a fluctuating phenomenon in the consumer goods industry sector companies listed on the Stock Exchange in 2014-2017. The population used as the object of observation is 23 consumer goods industry companies listed on the Indonesia Stock Exchange in the period 2014- 2017. Determination of research samples using purposive sampling method and obtain a sample of 43 consumer goods industry companies based on certain criteria. The results showed that the size of the company did not affect the company's value, leverage and profitability had a significant effect on the value of the company. In this study there were still many limitations and disadvantages, namely, the influence of the independent variable was only able to explain 79.6% so it needed additional other independent variables.